Civil avionic systems - Moir, I. (Aerospace series (Chichester, England), 2013)
Civil Avionics Systems, Second Edition, is an updated and in-depth practical guide to integrated avionic systems as applied to civil aircraft and this new edition has been expanded to include the latest developments in modern avionics. It describes avionic systems and potential developments in the field to help educate students and practitioners in the process of designing, building and operating modern aircraft in the contemporary aviation system. Integration is a predominant theme of this book, as aircraft systems are becoming more integrated and complex, but so is the econom.